Immediate effects of Aussie Current on chronic low back pain: a randomized controlled trial - Leticia Bobato; Gabriele Bressan; Lucas Vinicius Dias; Ramon Schmidt Sale; Audrin Said Vojciechowski; Luiza Helena Gonçalves; Ana Carolina Brandt de Macedo (Einstein (São Paulo))
ABSTRACT Objective: To analyze the immediate analgesic effects of Aussie Current on chronic low back pain using different parameters. Methods: A total of 105 patients (aged 18-80 years, of both sexes, with chronic low back pain) were randomized into five groups: AG1kHz/100Hz, AG1kHz/2Hz, AG4kHz/100Hz, AG4kHz/2Hz, and placebo. All participants underwent a single application of the Aussie Current for 30 min. The assessments were conducted before and immediately after the intervention, with the following outcomes: pain intensity using the numerical pain rating scale, McGill Pain Questionnaire, mechanical pain threshold, and five-times-sit-to-stand test before and immediately after the intervention. The Start-Back Questionnaire was administered before the intervention to analyze the physical and psychosocial factors related to chronic lower back pain. Results: In the intragroup analysis, all groups showed significant differences in the numerical pain rating scale and total McGill Pain Questionnaire index. For the mechanical pain threshold, a significant difference was observed in the AG1kHz/100Hz Group at three points in the lumbar region and in the five-times-sit-to-stand test at AG1kHz/100Hz, AG1kHz/2Hz, and AG4kHz/100Hz. In the intergroup comparison, there was a significant difference in the numerical pain rating scale scores between the AG1kHz/100Hz and AG1kHz/2Hz Groups in the Placebo Group. Conclusion: Aussie Current provides an immediate analgesic effect in individuals with chronic low back pain; however, there is no consensus on the ideal parameters. ClinicalTrials.gov Identifier: RBR-98HJ9X.